Expanding the doughnut? How the geography of housing demand has changed since the rise of remote work with COVID-19 - Ahrend, Rudiger (OECD Regional Development Papers, 2023)
The rise of remote working in connection with the COVID-19 pandemic may have reshaped people's preferences on residential locations, thus generating a new geography of housing demand. So far, the literature has mainly focused on what has become known as the "doughnut effect", the hollowing out of large metropolitan centres towards their respective suburban areas ("commuting zones"). However, changes in residential preferences might have affected urban and rural living in more nuanced ways. This paper shows that changes in relative house prices - a proxy for short-term changes in demand for home ownership ("housing demand") - have gone beyond the metropolitan boundaries, consistent with the idea of longer but less frequent home to work commuting. Interestingly, we are not seeing a re-emerging preference for rural life as such but, rather, a desire to move to places that combine the benefits of rural and urban life. In the areas outside the main metropolitan centres but within the commuting zones, housing demand has increased the most in low density, more affordable, settlements (rural). In contrast, beyond the boundaries of large metropolitan areas, where most space tends to be rural, housing demand has increased the most in high-density settlements (cities)